3D MnCo2O4@CoS nanoarrays with different morphologies as an electrocatalyst for oxygen evolution reaction. (13th August 2019) - Du, Xiaoqiang; Su, Hui; Zhang, Xiaoshuang
Abstract: The efficiency and stability of electrocatalysts are the key factors for measuring oxygen evolution reaction. In this work, the MnCo2 O4 structure assembled from well-arranged nanowires or nanosheet arrays has been grown vertically on nickel foam by in-situ hydrothermal method. Interestingly, different morphology of MnCo2 O4 can be easily regulated by adding NH4 F to a mixed solvent to achieve conversion from nanowires to nanosheets. In addition, further synthesis of unique three-dimensional hierarchical core/shell MnCo2 O4 @CoS nanowires or nanosheets arrays was performed primarily by electrochemical deposition. Both MnCo2 O4 @CoS-7 cycles nanowires and MnCo2 O4 @CoS-7 cycles nanosheets exhibit high efficiency and long-lasting stability for the oxygen oxidation reaction. The lower overpotential of only 280 mV and 270 mV at 20 mA cm −2 for the MnCo2 O4 @CoS-7 cycles nanowires and MnCo2 O4 @CoS-7 cycles nanosheets were obtained with lower Tafel slopes of 139. 19 mV dec −1 and 131.81 mV dec −1 in 1.0 M potassium hydroxide respectively comparing with our other MnCo2 O4 @CoS catalysts. The results demonstrate that the crystal morphology of MnCo2 O4 @CoS does not significantly influence their electrocatalytic activity in water oxidation reactions by comparing nanostructured MnCo2 O4 @CoS nanowires and MnCo2 O4 @CoS nanosheets. The high catalytic activity of the MnCo2 O4 @CoS nanoarrays is attributed to the possession of more active sites, larger specific surface area, abundant oxygen vacancy, and fast electron transport rate. Not only that, the durability of the MnCo2 O4 @CoS nanoarrays is also excellent after continuous oxygen evolution test of 1000 cycles. The results of XRD, SEM and XPS show that MnCo2 O4 @CoS-7 cycles nanowires and MnCo2 O4 @CoS-7 cycles nanosheets materials can be used as a highly efficient and stable catalyst for oxygen evolution reaction. Graphical abstract: The results of XRD, SEM and XPS show that MnCo2 O4 @CoS-7 cycles nanowires and MnCo2 O4 @CoS-7 cycles nanosheets materials can be used as a highly efficient and stable catalyst for oxygen evolution reaction.Image 1 Highlights: MnCo2 O4 @CoS is prepared by two-step hydrothermal and electrochemical deposition reaction. MnCo2 O4 @CoS can serve as electrocatalytic water oxidation catalysts. MnCo2 O4 @CoS presents an excellent long-term electrochemical durability.